2020
DOI: 10.1590/1807-3107bor-2020.vol34.0061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CPP-ACP on remineralization of artificial caries-like lesion: an in situ study

Abstract: The purpose of this double-blind, randomized, crossover in situ study is to compare remineralization of preformed enamel lesions by casein phosphopeptide-stabilized amorphous calcium phosphate (CPP-ACP) and fluoride dentifrice products. During each of four 10-day experimental legs, 10 participants wore intraoral removable palatal acrylic appliances with four human enamel slabs with preformed lesions. A 0.03-mL treatment paste was dripped extraorally onto the enamel blocks once a day for 3 min. The four randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 24 publications
3
32
0
Order By: Relevance
“…Like others, we found that fluoride toothpaste enhances EMH (Dai et al, 2019;Oliveira et al, 2020;Zhang et al, 2011). This might be related to the formation of fluorapatite on the enamel surface.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Like others, we found that fluoride toothpaste enhances EMH (Dai et al, 2019;Oliveira et al, 2020;Zhang et al, 2011). This might be related to the formation of fluorapatite on the enamel surface.…”
Section: Discussionsupporting
confidence: 88%
“…This might be related to the composition of the CPP–ACP, which functioned as a reservoir of Ca and PO 4 3− ions, and its ability to penetrate the subsurface lesions to form hydroxyapatite (Mehta et al, 2013). However, some researchers believe that there is a greater influence of fluoride than CPP–ACP on early caries lesions (Oliveira et al, 2020; Vyavhare et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At low pH, ACP separates from CPP, which usually increases the salivary saturation with Ca 2+ and PO 4 3− ions. After this separation, CPP can stabilize ACP in the oral biofilm, providing an amorphous state of supersaturation to maintain alkaline pH and enhance the remineralization process 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%